Prevalence of symptomatic deep vein thrombosis (DVT) in patients with temporary double lumen dialysis femoral catheterization-Experience from Multan institute of kidney diseases Multan (MIKD). - Bashir, Khurrum; Anwar, Shumaila; Rashid Asghar, Muhammad; Saleem, Nayyar (Pakistan Journal of Kidney Diseases, 2023)
Objective: The study was conducted in Multan institute of kidney diseases to explore the DVT prevalence after double lumen dialysis femoral catheterization for haemodialysis. Methodology: Retrospective cross sectional study was conducted in Multan Institute of Kidney Diseases, all double lumen dialysis femoral catheters passed over a period of five years (sep-2017 to sep-2022) were included in study, identified from electronic system of hospital. Except for those with temporary femoral catheters, all patients met the exclusion criteria. SPSS version 25 was used for data analysis and prevalence of DVT was calculated. RESULTS: Total 6628 patients with a mean age of 48(range 14 -90 years) were catheterized, 4105(61.9%) males and 2523(38.1%) were females, right sided catheters were 1826(27.5%) and 4802(72.5%) patients underwent left sided insertions. Duplex ultrasound was done of all symptomatic 252(3.8%) patients and femoral DVT was confirmed in 174(2.6%) that is 69% of symptomatic patients. The incidence of DVT significantly (3.7 fold) increase at day six and onward. Prevalence of DVT is 2.6% in all catheterized and 69% of symptomatic patients. Conclusion: Femoral vein remains an important emergency haemodialysis access route. Physicians inserting femoral venous catheters should be aware of the risk of lower extremity DVT from day three and consider performing duplex ultrasound examinations at day five and onwards if it is extremely necessary to be kept in situ for this duration, otherwise attention should be paid gaining access elsewhere at earliest possible opportunity.